1995
DOI: 10.1897/1552-8618(1995)14[251:fsapas]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

FACILE SYNTHESIS AND PHYSICAL AND SPECTRAL CHARACTERIZATION OF 2,6-DI-tert-BUTYL-4-NITROPHENOL (DBNP): A POTENTIALLY POWERFUL UNCOUPLER OF OXIDATIVE PHOSPHORYLATION

Abstract: The compound 2,6-di-tert-butyl-4-nitrophenol (DBNP), a potentially powerful uncoupler of ATP-generating oxidative phosphorylation, has been physically and spectroscopically characterized using X-ray crystallography, differential scanning calorimetry (DSC), thermal gravimetric analysis (TGA), GC-MS spectrometry, Fourier-transformed IR (FTIR) spectrophotometry, UV-Vis spectrophotometry, and FT 'Hand I3C-NMR spectroscopy. However, DBNP is not commercially available; therefore, it had to be synthesized in the labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…In the post‐reaction electronic absorption spectra a new band at λ =431 nm for X=CN (Figure S23) and λ =445 nm for X=NO 2 , (Figure S24) was observed. These new bands were tentatively assigned to the corresponding phenolate ions ( X ArO − ) . In fact, we observed that 1 also immediately reacted with 4‐NO 2 ‐2,6‐DTBP to form the corresponding phenolate ion, which showed a band at λ =445 nm (Figure S25).…”
Section: Resultsmentioning
confidence: 76%
“…In the post‐reaction electronic absorption spectra a new band at λ =431 nm for X=CN (Figure S23) and λ =445 nm for X=NO 2 , (Figure S24) was observed. These new bands were tentatively assigned to the corresponding phenolate ions ( X ArO − ) . In fact, we observed that 1 also immediately reacted with 4‐NO 2 ‐2,6‐DTBP to form the corresponding phenolate ion, which showed a band at λ =445 nm (Figure S25).…”
Section: Resultsmentioning
confidence: 76%
“…Rivera-Nevares et al reported that DBNP was second only to 3,5-di-tert-butyl-4-hydroxybenzylidene malononitrile in its action as an ATP uncoupler, based on quantum-mechanical calculations. (9) The effects of chronic exposures to DBNP at low concentrations will require further research.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first oxidative uncouplers to be studied was 2,4‐dinitrophenol (DNP). Other uncouplers of early interest were chlorinated and nitrated phenols 6, 7. Recently, it has been reported that 3, 3', 4′, 5‐tetrachlorosalicylanilide (TCS), a component in the formulation of soaps, rinses, and shampoos, etc, can reduce the transfer resistance of the cell membrane for protons, thus upsetting the balance of protons within the cell, resulting in excessive energy use for recovering this balance.…”
Section: Introductionmentioning
confidence: 99%